A review on recent advances in the enrichment of glycopeptides and glycoproteins by liquid chromatographic methods: 2016–Present. Issue 1 (25th November 2021) - Kumari, Mona; Tetala, Kishore K. R.
Abstract: Among various protein post‐translational modifications (PTMs), glycosylation has received special attention due to its immense role in molecular interactions, cellular signal transduction, immune response, etc. Aberration in glycan moieties of a glycoprotein is associated with cancer, diabetes, and bacterial and viral infections. In biofluids (plasma, saliva, urine, milk, etc.), glycoproteins are low in abundance and are masked by the presence of high abundant proteins. Hence, prior to their identification using mass spectrometry methods, liquid chromatography (LC)‐based approaches were widely used. A general enrichment strategy involves a protein digestion step, followed by LC‐based enrichment and desorption of glycopeptides, and enzymatic excision of the glycans. The focus of this review article is to highlight the articles published since 2016 that dealt with different LC‐based approaches for glycopeptide and glycoprotein enrichment. The preparation of stationary phases, their surface activation, and ligand immobilization strategies have been discussed in detail. Finally, the major developments and future trends in the field have been summarized.